Biological properties of lithium-containing surface pre-reacted glass fillers as direct pulp-capping cements. Issue 2 (February 2022) - Ali, Manahil; Okamoto, Motoki; Watanabe, Masakatsu; Huang, Hailing; Matsumoto, Sayako; Komichi, Shungo; Takahashi, Yusuke; Hayashi, Mikako
Highlights: Surface pre-reacted glass fillers containing lithium chloride are biocompatible with pulp tissues. Hydroxyapatite can be formed on these cements, resulting in good sealing with dentin. Li-containing surface pre-reacted glass fillers exhibit bactericidal and bacteriostatic activity against oral biofilms. Graphical Abstract: ga1 Abstract: Objective: Surface pre-reacted glass fillers (S-PRG) can release different types of ions and in our previous study, we modified these fillers with lithium chloride (S-PRG/Li-100 mM) to induce reparative dentin formation by activating the Wnt/β-catenin signaling pathway. Here, we assessed the biological performance of S-PRG/Li-100 mM and compared it with that of mineral trioxide aggregate (MTA) and S-PRG without additives. Methods: In vivo studies were conducted on male Wistar rats using Masson's trichrome staining in pulp-capped molars. The test materials were implanted subcutaneously to evaluate their capacity for vascularization and biocompatibility. The ability of the test materials to form apatite was tested by immersing them in simulated body fluid. Rhodamine-B staining was conducted to assess their sealing ability in bovine teeth, while their antibacterial activity was evaluated against Streptococcus mutans and Lactobacillus casei in terms of colony-forming units and by live/dead staining. Results: Masson's trichrome staining and tissue-implantation tests confirmed the biocompatibility of S-PRG/Li-100 mM and it was similar to that of MTA and S-PRG; inflammation regression was observed 14 days after operation in the subcutaneous tissues. S-PRG/Li-100 mM promoted the formation of apatite on its surface. Both the S-PRG groups showed higher sealing capability and bactericidal/bacteriostatic activity against oral bacterial biofilms than MTA. Significance: Lithium-containing surface pre-reacted glass cements exhibit better antibacterial and sealing capabilities than MTA, suggesting their potential as high-performance direct pulp-capping materials.